Inovasi Pembuatan Pempek Lenjer Ikan Bandeng (Chanos chanos), dan Puree Kacang Tunggak dengan Penambahan Jamur Tiram - Yurieta Deillena Riswanda; Any Sutiadiningsih; Asrul Bahar; Ita Fatkhur Romadhoni (Lembaga Pengembangan Kinerja Dosen, 2024)
This study uses experimental methods that aim to determine the interaction, proportion, addition, level of preference, and nutritional content in Pempek lenjer milkfish (Chanos chanos), and cowpea Puree with the addition of Oyster Mushrooms. covering organoleptic properties (shape, color, texture, aroma, and taste) in this type of research is experimental. Data collection techniques using observation methods. The independent variable of this study is the proportion of milkfish and cowpea puree (80%:20%, 70%:30%, and 60%:40%) as well as the addition of oyster mushrooms (20% and 10%). The dependent variable of the study was organoleptic sifaft. Control variables of this study include the type of material, equipment, and processing techniques. the best proportion of organoleptics was obtained from the treatment of 143 with very suitable characteristics. all criteria for assessing the best results in the assessment of preferences are found in treatment 143. The results of laboratory analysis of nutrient content of pempek lenjer 80%: 20%, 30% carbohydrate content of 44.65%, fat content of 3.40%, protein content of 11.05%, fiber content of 2.61%, ash content of 0.14%, and water content of 37.85%.